Male-Dominated Migration and Massive Assimilation of Indigenous East Asians in the Formation of Muslim Hui People in Southwest China - Wang, Qiyan; Zhao, Jing; Ren, Zheng; Sun, Jin; He, Guanglin; Guo, Jianxin; Zhang, Hongling; Ji, Jingyan; Liu, Yubo; Yang, Meiqing; Yang, Xiaomin; Chen, Jinwen; et al. (Frontiers in Genetics, 2021)
The origin and diversification of Muslim Hui people in China via demic or simple cultural diffusion is a long-going debate. We here generated genome-wide data at nearly 700,000 single nucleotide polymorphisms (SNPs) from 45 Hui and 14 Han Chinese individuals collected from Guizhou province in southwest China. We applied principal component analysis (PCA), ADMIXTURE, f-statistics, qpWave, and qpAdm analysis to infer the population genetic structure and admixture history. Our results revealed the Guizhou Hui people have a limited amount of West Eurasian related ancestry at a proportion of 6%, but show massive genetic assimilation with indigenous southern Han Chinese and Tibetan or Tungusic/Mongolic related northern East Asians. We also detected a high frequency of North Asia or Central Asia related paternal Y-chromosome but not maternal mtDNA lineages in Guizhou Hui. Our observation supports the cultural diffusion has played a vital role in the formation of Hui people and the migration of Hui people to southwest China was probably a sex-biased male-driven process.